Draft Second Five Year Plan Ajmer State 1956-1961 Volume II. - Planning Commission (Planning Commission, 1956)
The State of Ajmer covers an area of 2417 sq. miles with a population of 6,93,372. It has at present the following number of educational institutions of different categories.
Ajmer State